Gene and drug delivery system and potential treatment into inner ear for protection and regeneration - Kanzaki, Sho (Frontiers in Pharmacology, 2014)
The most common type of hearing loss results from damage to the cochlea including lost hair cells (HCs) and spiral ganglion neurons (SGNs). In mammals, cochlear HC loss causes irreversible hearing impairment because this type of sensory cell cannot regenerate. The protection from SGN from degeneration has implications for cochlear implant to patients with severe deafness. This review summarizes the several treatments for HC regeneration based on experiments. We discuss how transgene expression of the neurotrophic factor can protect SGN from degeneration and describe potential new therapeutic interventions to reduce hearing loss. We also summarized viral vectors and introduced the gene and drug delivery system for regeneration and protection of cochlear HCs. Finally, we introduce the novel endoscopy we developed for local injection into cochlea.